Coolfarming turn your great idea into the next big thing - Gloor, Peter A. 1961- (AMACOM American Management Association, 2011)
"Want to harness the power of new ideas? Become a 'coolfarmer'"--Resource description page.
Includes bibliographical references and index
Keywords: Creative ability in business; Technological innovations -- Management; New products -- Management; Créativité dans les affaires; Innovations; Gestion; BUSINESS & ECONOMICS; Development; Business Development; New products; Management; Technological innovations; Management